Application Of The Balanced Scorecard As A Measurement Model Of The Balance Of Stakeholder Value Proposition - Megawaty; Aminuddin Hamdat; Makkulawu Panyiwi Kessi, Andi; Panus (International Journal of Science, Technology & Management, 2022)
The balanced scorecard (BSC) is one of the concepts of a managerial performance measurement system that has a function and significance for companies carrying out strategic management by using four measurement perspectives in a systematic and integrated manner. This study uses the balanced scorecard, and management can identify, formulate, and create a value proposition that is balanced and proportionate among its stakeholders (stakeholders). This study aims to determine how the company's performance benchmarks and stakeholder value propositions use the balanced scorecard approach. The type and approach of this research are descriptive qualitative. The data analysis model is carried out in two ways: First, qualitatively, namely by describing according to language, sentences and perspectives to get a logical understanding and relevant to the research objectives. Second, using the balanced scorecard approach, namely data analysis made in numbers based on the balanced scorecard approach. This study explains how the general concept of the balanced scorecard, the four perspectives of measuring the balanced scorecard, the implementation of the balanced scorecard, and the balance of stakeholder value propositions. The results showed the measurement of the balanced scorecard at PT. "X" indicates that the company has a good set of benchmarks in implementing the balanced scorecard. The results also show that several balanced scorecard perspectives are proven to positively impact company performance in all views, including financial perspective, customer perspective, internal business process perspective, and learning and growth perspective. This study is due to the company's ability to correctly identify, formulate and determine stakeholder value propositions through a balanced scorecard approach.